Platelet-Derived Factor V Is an Important Determinant of the Metastatic Potential of Circulating Tumor Cells - Xin Deng; Xin Deng; Ziqian Feng; Ziqian Feng; Luochen Zhu; Luochen Zhu; Ni Chen; Ni Chen; Yifei Deng; Yongjie Li; Yongjie Li; Rong Li; et al. (Frontiers in Oncology, 2020)
Factor V (FV) is a critical component in the blood coagulation cascade. In patients, FV inhibitors have been reported to be associated with malignancy. FV is present in plasma and platelets, which exhibit physical and functional differences. However, the functions of FV in cancer progression remain poorly understood. We evaluated the impact of different levels of FV in plasma and platelets on the haematogenous mouse pulmonary metastasis model to determine whether FV determines the metastatic potential of circulating tumor cells. The role of platelet-derived FV was evaluated using a murine B16F10 pulmonary metastasis model, an assay of tumor cell adhesion to endothelial cells, and western blotting. By combining genetic models and FV inhibitory antibody, the transgenic mice with lower platelet FV expression showed significant increases in metastases compared with mice with higher platelet FV expression. In vitro, labeled B16F10 melanoma cells appeared to exhibit increased adhesion to endothelial cells that were treated with lower levels of platelet FV, but not platelet-poor plasma. Furthermore, platelets from mice with lower platelet FV levels expressed TFPIα at lower levels than with mice with higher platelet FV expression. Based on these findings, platelet-derived FV contributes to haematogenous pulmonary metastasis and is associated with the regulation of tumor cell adhesion to the vessel wall.